Higher Blood Urea Nitrogen and Urinary Calcium: New Risk Factors for Diabetes Mellitus in Primary Aldosteronism Patients - Liu, Yu; Zhou, Liang; Liu, Zhenghuan; Ma, Yucheng; Lin, Lede; Zhu, Yuchun; Wang, Kunjie; Li, Hong (Frontiers in Endocrinology, 2020)
Purpose The aim of the study was to investigate the prevalence and risk factors of diabetes mellitus (DM) in primary aldosteronism (PA) patients. Methods This case-control study enrolled 259 PA patients in West China Hospital, China from January 2016 to January 2019. Patients were divided into three groups: PA group, PA + impaired fasting glucose (IFG)/impaired glucose tolerance (IGT) group and PA + DM group. Clinical characteristics (like age and gender) and laboratory variables (like plasma aldosterone concentration and plasma renin activity) were compared between three groups. Univariate and multivariate logistic regression analyses were performed to determine risk factors for DM in PA patients. The association of random blood glucose with the above-mentioned factors were also investigated by Pearson correlation analyses. Nomogram model was developed to predict the probability of DM in PA patients. Results 49 (18.9%) patients were diagnosed with DM and 22 (8.5%) with IFG/IGT in 259 PA patients. Apart from older age, male, higher body mass index, higher triglycerides and lower cholesterol, we found that higher blood urea nitrogen (BUN) and higher 24h urinary calcium (Ca) might be potential new risk factors for dysglycemia. The nomogram model for DM in PA patients had a good predictive accuracy, with the area under the curve of receiver operating characteristic of 0.839 (95% CI 0.784-0.893). Conclusions PA patients were more likely to have DM compared with general population. Apart from older age, overweight and dyslipidemia, higher BUN and excessive excretion of urinary Ca may also be the new potential risk factors for DM in PA patients.